A study of multibody modeling and calibration method for FMVSS 208 rollover test. Issue 6 (2nd November 2019) - Mo, Yimin; Shen, Peng; Lv, Juncheng; Lin, Zhigui; Liang, Yongbin; Liu, Changye
Abstract: Finite element simulation technology has been widely used in vehicle safety research. However, compared with other vehicle collision accidents, finite element model (FEM) used for passive safety research of rollover cannot be accepted generally due to its relatively long computation time. Aimed at the issue, this article proposes a kind of multibody modeling method based on FEM and test results. First, taking an example of the minivan, vehicle body is divided into suspension system, deformable upper body, and rigid lower body, and each part is constructed using MADYMO (a multibody dynamic software). Detailed modeling steps of each part are provided. Second, the upper body of model is corrected by static pressure test on vehicle top conducted in accordance with FMVSS 216, and the correspondence of output response of acceleration of B-pillar and centroid angular velocity between simulation model and FMVSS 208 rollover test is evaluated by ISO/TS 18571. The quantitative correspondence score is taken as optimization objective to calibrate uncertain parameter of MADYMO model. Finally, the correctness of MADYMO model and effectiveness of model calibration method are verified after comparison with test results of FMVSS 208. The result verifies that multibody vehicle rollover model created with this method can provide simulation with relatively high accuracy and present key deformation of vehicle body, meanwhile saving massive calculation time, which provides reliable simulation model for passenger damage research and vehicle safety performance optimization in subsequent process. The proposed method is general and universal modeling and calibration method, suitable for other vehicle.